Marriage Tradition of Indigenious Community of Baduy and The Covid-19 Prevention - Farida Patittingi1, Desti Novita2, Kahar Lahae1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Baduy is a group of people who are still primitive, because they still survive with the principles of a longlife full of local wisdom, including in conducting marriage rituals. However, the problem with maritalprocedures is contrary to positive law in Indonesia. In addition, the marriage ceremony conducted by theBaduy indigenous people involves many people which is also contrary to government policies regardingsocial distancing in handling the Covid-19 outbreak. The purpose of this study is (1) to analyze the maritalstatus carried out by the Baduy community in positive law in Indonesia, (2) to analyze the efforts of theBaduy community to prevent the spread of covid-19 in the midst of procuring a marriage ritual that involvesmany people. The method in this paper uses normative juridical research and uses three sources of legalmaterial, namely primary, secondary and tertiary. Data analysis was performed descriptively qualitative. Theresults showed that (1) the legality of the marriage of the Baduy community certainly had no legality and thismarriage was not recognized by the state, (2) the marriage ceremony of the Baduy community could still becarried out as usual, bearing in mind that this community was very closed with the outside world long beforethe Covid-19 pandemic, but this clearly cannot be applied in outside Baduy communities which incidentallystill open access for outsiders to visit